TANGGAPAN WISATAWAN TERHADAP ATRAKSI WISATA PADA EVENT LAMPU COLOK DI KABUPATEN BENGKALIS - Kurnia Farozita; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Bengkalis has tourism potential such as nature tourism, cultural tourism, religious tourism and historical tourism. Event Lampu Colok is held on the 27th of Ramadan until the evening of Eid. Therefore, this study was conducted to find out how the response of tourists to tourist attractions in the event of lights colok in Bengkalis to increase the number of tourist visits in Bengkalis Regency.This study aims to find out how to illustrate the Event of Lampu Colok and find out how Tourist Response Terhdap Tourist Attraction On Event Lampu Colok in Bengkalis Regency. This research uses quantitative descriptive method to examine the problem in the lift by analyzing the response of tourists who come to see Lampu Colok. The questionnaires were distributed as many as 30 people. While data collection techniques in this study using observation, interviews, questionnaires, and documentation.The results of this study indicate that the response of tourists to tourist attraction on the event of Lampu Colok in Bengkalis Regency is ssetuju with the overall score that is the amount of 1098, and this result is obtained in the range of score 918 - 1133. In doing this Lampu Colok event aims to preserve the tradition of the Regency Bengkalis.Event Lampu Colok displays works very good because this Lampu Colok is formed into mosques, calligraphy, canoe and others. And Lampu Colok is made of bottle or tin of beverage which is then processed into a lamp by adding axis and kerosene as its fuel, so it displays very good work.Keywords : Event, Lampu Colok, Tradition in Bengkalis